Climatic hazards in coastal Bangladesh : non-structural and structural solutions - Paul, Bimal Kanti (Kidlington, UK ; Cambridge, MA : Butterworth-Heinemann an imprint of Elsevier, 2017)
Coastal Hazards in Bangladesh: Non-Structural and Structural Solutions provides a review of the study of Bangladesh's coastal region, an area whose location and physical geography present the prefect microcosm for the study of coastal hazards and for the development of tactics that are applicable to regions around the world. The book presents engineers, scientists, and planners with the necessary tools and planning solutions used to combat coastal vulnerabilities in Bangladesh. Divided into seven chapters, it begins with a critical overview of cyclone and storm surge disasters, focusing on both engineering responses and public preparedness programs to such events. In addition, engineering recommendations are provided for further reduction of their impacts, such as erosion, accretion, and land subsidence, and numerical models are introduced to assess flood induced hazard and risk, flood-induced design loads, and how to intervene in protecting key installations, infrastructures, and communities.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 7, 2016).
Keywords: Climatic changes -- Bangladesh; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Climatic changes; Bangladesh; Electronic books; Electronic books